Science Teaching at a Distance in Greece: Students' Views - Constantina Stefanidou; Achilleas Mandrikas (MDPI AG, 2023)
This article presents in a comparative way the findings from two surveys conducted on primary (students in Y6) and secondary (students in Y10) students in Attica, Greece, in order to map their views on distance science education, which was emergently implemented due to the COVID-19 outbreak during the school year 2020-2021. The research was conducted in a sample of 378 primary and 197 secondary students. The findings revealed that students were not satisfied with the distance teaching and learning of science, either in primary or in secondary education, except for the increased use of audiovisual material. Technical issues, such as poor network and infrastructure, lack of face-to-face interaction with classmates and teacher, external and internal distractions, lack of sufficient experimental activities, and limited understanding of concepts were common findings in both levels of education. Concerning the differences between the levels, it seems that in primary education more technical problems were reported, while in secondary education more didactic problems were reported.